To design and fabricate of an innovative multipurpose hand truck / Muhammad Danish Dzulhelmy - Dzulhelmy, Muhammad Danish (2022)
The study of manufacturing is necessary to conduct this project to make sure that students understand about process that should be done for this project. The project is about designing and fabricating a Multipurpose Hand Truck. This project aimed to help manage loads without damaging the body and lower the risk of injury. Other than that, the purpose of this project are also to save money, time and storage space. The steps taken to achieve this goal included, sketching the product design, creating a CAD model of the design, and machining process such as grinding, drilling and cutting by considering ergonomic factors so that the users can use it easily. At the conclusion of the project, the multipurpose hand truck can make the users feel comfortable and easier to use it in daily life.